Long-Term Impacts of Post-weaning Social Isolation on Nucleus Accumbens Function - Bendersky, Cari J.; Milian, Allison A.; Andrus, Mason D.; De La Torre, Ubaldo; Walker, Deena M. (Frontiers in Psychiatry, 2021)
Adolescence is a period of incredible change, especially within the brain's reward circuitry. Stress, including social isolation, during this time has profound effects on behaviors associated with reward and other neuropsychiatric disorders. Because the Nucleus Accumbens (NAc), is crucial to the integration of rewarding stimuli, the NAc is especially sensitive to disruptions by adolescent social isolation stress. This review highlights the long-term behavioral consequences of adolescent social isolation rearing on the NAc. It will discuss the cellular and molecular changes within the NAc that might underlie the long-term effects on behavior. When available sex-specific effects are discussed. Finally by mining publicly available data we identify, for the first time, key transcriptional profiles induced by adolescence social isolation in genes associated with dopamine receptor 1 and 2 medium spiny neurons and genes associated with cocaine self-administration. Together, this review provides a comprehensive discussion of the wide-ranging long-term impacts of adolescent social isolation on the dopaminergic system from molecules through behavior.